2021
DOI: 10.14414/jebav.v24i1.2477
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Workplace Spirituality, Perceived Organizational Support, and Innovative Work Behavior: The Mediating Role of Psychological Well-Being

Abstract: This research investigating the innovative work behavior of teachers and school staff during the Covid-19 pandemic is still rarely studied, so it has contributed to improving the behavior of teachers and school staff in Indonesia during the Covid-19 pandemic. The purpose of this study was to analyze and examine the direct influence of workplace spirituality and perceived organizational support on the innovative work behavior of teachers and school staff. Besides, exploring the mediating role of psychological h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…According to Ciptaningtyas (2018), psychological well-being is favorably associated to work atmosphere. Masyhuri et al (2021) discovered that psychological well-being mediates the relationship between workplace spirituality and perceived organizational support for creative activity.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ciptaningtyas (2018), psychological well-being is favorably associated to work atmosphere. Masyhuri et al (2021) discovered that psychological well-being mediates the relationship between workplace spirituality and perceived organizational support for creative activity.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…According to Shahid et al (2016)'s research, particularly social ties, have a strong beneficial influence on innovative work behavior, and well-being has been demonstrated to modulate the effect of social interactions on innovative work behavior. Masyhuri et al (2021) study emphasizes the significance of psychological well-being as a moderating component in affecting creative work behavior. According to the findings of this study, workplace spirituality and perceived organizational support have a direct impact on innovative work behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of mediation analysis of job stress in a relationship between workplace spirituality and psychological well-being were significantly negative [ 51 , 52 , 96 ], since it negatively mediates the relation between workplace spirituality and psychological well-being, meaning that with a high level of workplace spirituality, the job stress level will be low, then the psychological well-being level will be high, and vice versa [ 44 , 50 , 71 ]. Therefore, the findings reflect that job stress should be reduced to achieve optimal performance from university teachers, and job stress damages the psychological well-being of a university teacher [ 38 , 52 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature also substantiated that the conducive working environment of an organization alleviated psychological well-being in terms of organizational value and alignment of personal values [ 59 , 76 , 97 ]. Finally, the mediation of personal growth also enhances the psychological well-being of a university teacher with spiritual orientation [ 71 , 96 , 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in previous literature that employees who are highly engaged in their jobs are more creative and innovative in terms of the work behaviors. Further, Masyhuri, Pardiman [ 67 ], reported that school teachers with high level POS and psychological well-being are found highly productive. The psychological well-being as an essential part of overall social atmosphere become increasingly important part of well-designed employer value proposition in enterprises [ 17 ].…”
Section: Literature Review Proposed Hypothesis and Frameworkmentioning
confidence: 99%